A Disease in Disguise-A Case Report on an Atypical Presentation of Bowen's disease - E.P Raj Kirit; Ananthula Saketha; Sasi Kiran Attili; Sridevi Ponugupati (Nepal Journal of Dermatology, Venereology & Leprology)
Bowen’s disease (BD) is a rare premalignant condition. The etiology of Bowen’s disease is